A consciência, o incentivo e o método como instrumentos de promoção da sustentabilidade a partir da ruptura do modelo de desenvolvimento clássico: viabilizando a gestão energética dos resíduos decorrentes do consumismo - Eduardo, Thales José Pitombeira (2015)
The purpose of this study is to assess to what extent the concept of sustainable development has proved difficult to implement, proposing to rebuild on the environmental crisis, here cut to the problems arising from the excessive and irrational consumerism. It starts with the premise that sustainability does not enjoy specificity able to give rise efficient behaviors to real protection, particularly with regard to waste management. Therefore, the main instruments capable of generating a reactive change in the economic and social framework are supported on a tripod, namely, awareness, encouragement and the method. Although with advances, the problem is still shrouded by the taint of conformity, the protective fallacious speech by impracticality. It is considered necessary a way of thinking that goes against the market system created to quantify the needs and value the social happiness by utilitarianism. The real sense of having ceases to be characterized by purely private aspect, the individual contentment, projecting into collective dimensions, considering that the practice of sustainable consumption, in order to promote waste management, warranty manifestation of expression the rational use of environmental goods and resources, is pleased to diffuse interests. In this context, the gradual breakdown of classic economic development model for sustainable is analyzed in parallel to the scientific revolutions that adjetivam the endless cycle of sedimentation and proof of knowledge. Then encourage the practice of reverse logistics in the economic and industrial sector through fiscal and financial measures, strengthen the management of waste because they favor the reuse of discarded materials after the consumer relationship, the product manufacturing process. This strategy is presented as temporary, to enter the no culture of waste until it is freely practiced. Finally, one comes to the analysis of the method, which is expressed in the adoption of techniques to promote sustainability. They are in the technology plan developed by a sensible policy to the principle of efficient allocation of natural resources for the provision of public services. We speak, therefore, a significant reduction of investments in non-alternative energy sources, such as hydropower, for example, and the option for sustainable solutions, as the production of energy through methane originating from the digestion of waste. Finally, the diversification of energy sources, this complex reality, ensure energy security, in that it focuses not only on non-alternative and non-renewable sources. The research is based on descriptive, explanatory and dialectical methods and draws on research in bibliographic and documentary data.